2018
DOI: 10.1177/0022034518792870
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Hypomineralized Second Primary Molars: A Prospective Twin Study

Abstract: The etiology of hypomineralized second primary molars (HSPM) is unclear, but genetic and environmental factors have been proposed. The aim of this study was to investigate the relative contribution of genes and environment to the etiology of HSPM and to identify potential environmental risk factors in a longitudinal twin cohort. Children from twin pregnancies ( N = 250) were recruited antenatally, and detailed demographic, health, and phenotypic data were collected at recruitment, 24- and 36-wk gestation, birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 32 publications
3
38
0
6
Order By: Relevance
“…This model fits very well with MIH from what is known from the literature regarding variation in frequency, depending on geographic origin [Vieira and Kup, 2016], variation in severity and clinical presentation [Vieira and Kup, 2016], and no clear aggregation in families for most of the cases, although approximately 20% of families have additional affected family members [Jeremias et al, 2016]. Twin studies indeed showed a higher concordance rate for monozygotic twins in comparison with dizygotic ones both in the classic presentation of MIH [Teixeira et al, 2018] and in hypomineralized second primary molars [Silva et al, 2019]. Based on the figures published by Teixeira et al [2018], we could calculate that the amount of MIH variation in the population that can be explained by genetics is approximately 20% [Vieira, 2019].…”
Section: Introductionsupporting
confidence: 79%
“…This model fits very well with MIH from what is known from the literature regarding variation in frequency, depending on geographic origin [Vieira and Kup, 2016], variation in severity and clinical presentation [Vieira and Kup, 2016], and no clear aggregation in families for most of the cases, although approximately 20% of families have additional affected family members [Jeremias et al, 2016]. Twin studies indeed showed a higher concordance rate for monozygotic twins in comparison with dizygotic ones both in the classic presentation of MIH [Teixeira et al, 2018] and in hypomineralized second primary molars [Silva et al, 2019]. Based on the figures published by Teixeira et al [2018], we could calculate that the amount of MIH variation in the population that can be explained by genetics is approximately 20% [Vieira, 2019].…”
Section: Introductionsupporting
confidence: 79%
“…Hypomineralization was diagnosed in 7.3% of the primary second molars in this study. The literature reported values ranging from 3.6% to 10.2% . This prevalence was considered high, and this is a cause for concern, since the HSPM may increase the risk of dental caries by 3 to 6.34 times …”
Section: Discussionmentioning
confidence: 99%
“…The literature reported values ranging from 3.6% to 10.2%. 1,4,6,7,12 This prevalence was considered high, and this is a cause for concern, since the HSPM may increase the risk of dental caries by 3 to 6.34 times. 4,26 HSPM can affect between 1 and 4 primary second molars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers are using/have used the index, but its properties, in terms of validity and reproducibility, are yet to be tested. As with any new index, the MIH/HSPM index needs to demonstrate adequate reproducibility (ie reliability) and validity to be used for clinical assessment.…”
Section: Introductionmentioning
confidence: 99%